Can plant‐derived phytochemicals provide symptom relief for hair loss? A critical review - Daniels, G.; Akram, S.; Westgate, G. E.; Tamburic, S. (International journal of cosmetic science, 2019)
It is known that hair growth disorders and hair loss can cause personal distress and affect well‐being. Whilst clinical conditions remain a target for medical research, current research on hair follicle biology and hair growth control mechanisms also provides opportunities for a range of non‐medical and cosmetic interventions that have a modulating effect on the scalp and follicle function. Furthermore, an improvement of the hair fibre characteristics (cuticle structure, cortex size and integrity) could add to the overall positive visual effect of the hair array. Since phytochemicals are a popular choice because of their traditional appeal, this review provides a critical evaluation of the available evidence of their activity for hair benefit, excluding data obtained from animal tests, and offers recommendations on improving study validity and the robustness of data collection in pre‐clinical and clinical studies. Résumé La perte des cheveux ou les troubles de la croissance sont connus pour engendrer une grande détresse et affecter le bien‐être des individus. Bien que les maladies soient la cible principale de la recherche médicale, de récentes découvertes sur la biologie du follicule pileux et les mécanismes de contrôle de la pousse de cheveux pourraient donner lieu à des interventions non‐médicales ou cosmétiques afin d'impacter le cuir chevelu et le follicule. De plus, améliorer les caractéristiques de la fibre capillaire (structure des cuticules, taille et intégrité du cortex) pourrait contribuer à embellir l'apparence de la masse capillaire. Les phytoingrédients sont populaires car traditionnellement utilisés dans les cosmétiques, et cette revue présente une évaluation critique de leurs bénéfices pour les cheveux, en excluant les données issues de tests sur les animaux. Des recommandations afin d'améliorer la collecte de données et la validité des études pré‐cliniques et cliniques sont aussi présentées dans cette revue.